Global Maritime Surveillance by Airliner-Based AIS Detection: Preliminary Analysis. (November 2015) - Plass, Simon; Poehlmann, Robert; Hermenier, Romain; Dammann, Armin
<x content-type="archive" xml:space="preserve">Abstract</x> Demands on security, safety, and environmental protection in worldwide shipping are steadily increasing. Shipboard broadcast transponders based on the Automatic Identification System (AIS) can be easily detected close to coastal or waterway areas. Satellite-based AIS receivers detect globally but are limited in high-density traffic areas. This paper investigates the challenges and performance of AIS detection on aircraft at altitudes between 8 500 m and 10 000 m. During flight trials over sea and land, AIS signals were recorded. Post-processing of the recorded data allows the evaluation but also faces challenges due to the nature of overlapping AIS signals at the aircraft. A comparison of detected signals at the aircraft with received AIS signals on the ground is given, including the evaluation of the reception footprint of the aircraft. Finally, a concept for worldwide AIS detection via airliners is presented. The study shows the potential for global complementary surveillance coverage via airliner-based AIS detection.